2019
DOI: 10.1021/acs.orglett.9b01836
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Regio- and Stereoselective Hydrosilylation of 1,3-Diynes To Access Silyl-Functionalized 1,3-Enynes

Abstract: A regio- and stereoselective hydrosilylation of 1,3-diynes has been developed relying on catalysts generated from bench-stable Co­(acac)2 and dppp ligand. A variety of symmetrical and unsymmetrical 1,3-diynes undergo this transformation, yielding the corresponding silyl-functionalized 1,3-enynes in high yields with excellent regioselectivity. Gram-scale reactions and further transformations of the silyl-containing 1,3-enyne products highlight the synthetic utilities of this Co-catalyzed hydrosilylation of 1,3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…Therefore, considering the reaction methodology, conditions, and application of a specific type of catalyst (often tailored-made) is of prior importance, especially when such complex diyne molecules are used as reagents. 68,73,74,156,163 The simplicity of the hydrosilylation process, its high tolerance towards various functional groups present in the reagent structures, as well as the diversity of the selectivities, which can be tuned by the proper choice of the catalyst, has rendered this transformation the first choice for the synthesis of organosilicon compounds. The reactivity of the silyl group in coupling reactions or desilylation processes has allowed the application of the resulting compounds (e.g., 1,3-enyne or 1,3-diene fragments), in the synthesis of natural or biologically active compounds.…”
Section: Hydrosilylationmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, considering the reaction methodology, conditions, and application of a specific type of catalyst (often tailored-made) is of prior importance, especially when such complex diyne molecules are used as reagents. 68,73,74,156,163 The simplicity of the hydrosilylation process, its high tolerance towards various functional groups present in the reagent structures, as well as the diversity of the selectivities, which can be tuned by the proper choice of the catalyst, has rendered this transformation the first choice for the synthesis of organosilicon compounds. The reactivity of the silyl group in coupling reactions or desilylation processes has allowed the application of the resulting compounds (e.g., 1,3-enyne or 1,3-diene fragments), in the synthesis of natural or biologically active compounds.…”
Section: Hydrosilylationmentioning
confidence: 99%
“…Depending on the type of the catalyst, reagents, their concentration, ratio, and process conditions, silylated 1,3-enynes, 1,3dienes, or allenes can be formed, frequently as a complex mixture of products (up to nine different compounds can potentially be formed). 62,73,74,156,164 Many papers describe the hydrosilylation of monoalkynes, 14,41,48,49,51 but the addition of the Si-H bond to 1,3-diynes is much more demanding and limited only to a few papers. The hydrosilylation of 1,3-diynes occurs mainly in the presence of noble metal complexes (Rh, Pt, Pd, Ru).…”
Section: Hydrosilylation Of Conjugated 13-diynes Towards Molecular and Macromolecular Unsaturated Organosilicon Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…[8b] Considering complete lack of chiral catalysts for asymmetric hydrosilylation/cyclization of 1,6-enynes to synthesize enantioenriched cyclic alkylsilanes,w eb ecome particularly interested in identifying chiral cobalt catalysts for the synthesis of such chiral cyclic alkylsilane compounds during our continuous effort in developing cobalt-catalyzed hydrosilylation reactions of unsaturated hydrocarbons. [11] Herein, we report cobalt-catalyzed asymmetric hydrosilylation/cyclization of 1,6-enynes that yields chiral alkylsilane or vinylsilane products with excellent enantioselectivity.W ea lso showed that chiral organosilane products from these reactions can be converted to avariety of chiral heterocyclic compounds via stereospecific transformations of either SiÀHorCÀSi bonds.Mechanistic studies reveal the chelation of 1,6-enynes to cobalt catalysts and the factors that control the regioselectivity of this cobalt-catalyzed hydrosilylation/cyclization of 1,6-enynes.…”
Section: Introductionmentioning
confidence: 99%